Aplicação da Análise Geoestatística para Modelagem Espacial do Mercúrio e Matéria Orgânica em Solos Florestais na Amazônia Ocidental - Bernardi, José Vicente Elias [UNESP]; Neira, Marcos Paulo; Manzatto, Angelo Gilberto [UNESP]; De Holanda, Igor Bruno Barbosa; De Almeida, Ronaldo; Bastos, Wanderley Rodrigues; Dórea, José Garrofe; Landim, Paulo Milton Barbosa [UNESP]; Vieira, Ludgero Cardoso Galli (My University, 2015)
This study was conducted in the Western Amazon, in an area located on the campus of the Federal University of Rondônia in Porto Velho, Rondônia. Were analyzed in soil samples of mercury (Hg) and organic matter (OM) concentrations in a stretch of open rain forest. The average Hg concentration was 150 ± 28□g.kg-1, whereas the concentration of OM was approximately 21.87 ± 5.87%. The method used to obtain the spatial distribution patterns of Hg and OM concentrations was the indicator kriging (KI), which showed that the occurrence of Hg distribution patterns obeys controlled by geological factors in the region, rich in granitic rocks, and the morphological parameters such as soil texture clay, which has a high degree of adsorption of heavy metals. The distribution of OM in turn, is related to the large amount of litter accumulated on the soil surface, together with the presence of microorganisms, fungi and small invertebrates. The conversion of this material into humus favors vegetation growth and its high concentration influences the amount of heavy metals in soil. The model set variography showed spatial dependence among the mercury levels in the soil of the area studied in relation to the use of the bygone area. The OM and Hg determination was approximately of 0.173 and significant (p = 0.0001).
Application of geostatistical analysis for spatial modelling of mercury and organic matter in soils of Western Amazon forest
Keywords: Geostatistics; Indicative kriging; Organic matter; Western Amazonia